Distribution of Volume Backscattering Strength of Fish Using Acoustic Method in Toba Lake, North of Sumatera - Syafura, Titi; Brown, Arthur; Isnaniah, Isnaniah (Fakultas Perikanan dan Kelautan Universitas Riau, 2020)
Toba in the past few years has declined in fish catching populations. In order to find out the fisheries of lake Toba with quickly used the acoustic methode using the de-tected backscattering strength volume of fish. The amis of this research is to determine the distribution of spatial backscattering strength of fish in the lake toba. The research was carried out in the lake toba using scientific echosounder DT-X split beam re-cording device 38-1000 KHz during six days in September. The results of the acoustic data processing showed that the highest Sv value was at depth of 50-75 m which is -32, 29 (dB) and the average is -55,82 (dB), Sv was detected on the eastern edge of lake toba waters, while the lowest Sv was detected at depth of 25-50 m which is 60.00 (dB) with the mean is -57,93 (dB) spread over the edge of the southern part of lake toba. This is influenced by the condition of the aquatic enviroment an habits of fish in the lake toba.